2011 16th International Solid-State Sensors, Actuators and Microsystems Conference 2011
DOI: 10.1109/transducers.2011.5969179
|View full text |Cite
|
Sign up to set email alerts
|

Development of a strain sensor for rolling contact loads

Abstract: Development of a strain sensor for rolling contact loads. -A strain sensor for high spatial resolution and low response time for rolling contact loads was developed and applied to an axial cylindrical roller bearing. The sensor consists of 100 nm thick titanium and is embedded in an aluminum oxide layer of 500 nm thickness that acts as a wear resistant and insulating layer. For an easy transfer of the process to radial surfaces only one photolithographic step is used.The sensor was characterized and compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…From the literature it was found that aluminum oxide (Al 2 O 3 ) has a thermal expansion co-efficient of 8 × 10 −6 K −1 , similar to steel, and a high mechanical dielectric strength of 9.9-15.8 kV mm −1 . It was also found that sputtered Al 2 O 3 has a very good adhesion to steel (Winkelmann et al, 2011). Due to its good thermal and mechanical properties and good adhesion to steel, it was chosen as the suitable isolation layer.…”
Section: Materials Selectionmentioning
confidence: 99%
“…From the literature it was found that aluminum oxide (Al 2 O 3 ) has a thermal expansion co-efficient of 8 × 10 −6 K −1 , similar to steel, and a high mechanical dielectric strength of 9.9-15.8 kV mm −1 . It was also found that sputtered Al 2 O 3 has a very good adhesion to steel (Winkelmann et al, 2011). Due to its good thermal and mechanical properties and good adhesion to steel, it was chosen as the suitable isolation layer.…”
Section: Materials Selectionmentioning
confidence: 99%
“…There are several reasons for this. We would like to mention the most important of these: the need to measure at even smaller spots to limit parasitic influences on the results of a measurement and also to obtain a higher degree of system comprehension [1,2]. In addition, geometrical circumstances like curved surfaces or limited space might prevent the use of conventional sensor designs [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Under the sponsorship of the scientific center Integrated Solutions in Sensorial Structure Engineering (ISIS), Winkelmann et al (2011) made an approach for a pressure sensor for high-load applications. The sensor was integrated into a conventional bearing washer and used Al 2 O 3 films as isolating layers (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, the DLC film could act for direct determination of stresses through a piezoresistive effect (Biehl et al, 2006;Peiner et al, 2006;Tibrewala et al, 2006) or as an isolating and a wear resistance covering layer (Nguyen et al, 2009). Under the sponsorship of the scientific center Integrated Solutions in Sensorial Structure Engineering (ISIS), Winkelmann et al (2011) made an approach for a pressure sensor for high-load applications. The sensor was integrated into a conventional bearing washer and used Al 2 O 3 films as isolating layers (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation